1864 Idaho Sess. Laws 441 - (:unkn) unknown (My University, 1864)
Ch. 3 § 35: Prohibited fighting a duel with a rifle, shotgun, pistol, Bowie-knife, dirk, small sword, back sword, or any other dangerous weapon. Should the opponent die of a wound within one year of the duel, the offender is deemed guilty of murder in the first degree. Other persons dueling with or without deadly weapons punished by prison term not less than two but no more than five years.
Keywords: DUELING